Implementation of the Discovery Learning Model to Increase Student Learning Motivation at Alue Bata Public Elementary School - Husniah; Erna Hastria (MANDAILING GLOBAL EDUKASIA, 2025)
This research was carried out to increase the learning motivation of grade V students of SD Negeri Alue Bata, Tadu Raya District, Nagan Raya Regency through the application of the discovery learning model. The background of this research is the low motivation of students in the learning process, which is characterized by passive student involvement, low curiosity, and the tendency of learning that is still teacher-centered. The type of research used is Class Action Research (PTK) which is carried out in two cycles. The research subjects amounted to 25 students, consisting of 16 males and 9 females. The research procedure includes the stages of planning, implementation, observation, and reflection. Data was collected through observation, questionnaires, tests, and documentation, then analyzed descriptively, qualitatively, and quantitatively. The results of the study showed an increase in student learning motivation from pre-cycle to cycle II. In the pre-cycle, most students have not shown interest and activeness in learning. After the implementation of discovery learning in the first cycle, learning motivation increased even though it was not evenly distributed. In cycle II, students are more active in asking questions, answering, and participating in learning activities. The conclusion of this study is that the application of the discovery learning model has proven to be effective in increasing the learning motivation of grade V students of SD Negeri Alue Bata.